Cold Iron and Lady Godiva : Engineering Education at Toronto 1920-1972. - Harris, Robin, S. (Heritage., 1973)
The Faculty of Applied Science and Engineering at the University of Toronto is celebrating its 100th anniversary. This informal volume examines the development of the Faculty, its changes over the last half century, the impact of this school on the community and nation, and a look into the future of engineering education.